STATISTICAL MODELLING OF RANDOM FIELDS ON THE PLANE USING SPLINE APPROXIMATION (ON EXAMPLE OF AIRMAGNETIC DATA) - VYZHVA, Z.; DEMYDOV, V.; VYZHVA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Іt is proposed to apply methods of statistical simulation of realizations of random processes and multi-dimensional random functions (random fields), to solve the problems of conditional maps, adding of data to achieve the necessary precision, and other such problems in geophysics. It is divided into deterministic and random components for data analysis. The deterministic component is proposed to approximate by cubic splines and the stationary random component is proposed to modeling on the basis of spectral expansions of random fields. Model example – aeromagnetic data two dimension field.